A study of risk factors of hepatitis B infection among rural adult population of Patna, Bihar - Lohani, Pallavi; Kumar, Alok; Singh, Rashmi; Kumar Sinha, Ranjeet; Mukherjee, Madhumita (International Journal Of Community Medicine And Public Health, 2017)
Background: Chronic infection with heptitis B virus (HBV) leading to cirrhosis, cancer, premature death and consequent economic burden is a global problem. Prevention is a public health challenge especially in unvaccinated and disadvantaged populations with unknown risk factors. Majority of Bihar’s population is rural, whose risk factors have not been studied earlier. The objective was to study the risk factors of HBV infection in the rural adult population of Bihar with aim of identifying target group for prevention. Methods: Analytic case-control study in which health camps were organized in villages of Phulwarisharif block of Patna district to screen adults and identify cases and controls. Results: H/o jaundice 6 months or more (p=0.00, OR=3.58); contact with HBV (p=0.00, OR=4.17), family H/o HBV (p=0.00 OR=5.41); blood transfusion (p=0.00, OR=6), H/o hospitalization (p=0.001, OR=2.36), surgery (p=0.003, OR=2.17) and migration (p=0.018, OR=1.95) were significant risk factors. Lack of knowledge about HBV was significant (p<0.030). About 40% and 20% of both cases and controls were aware of parenteral and sexual transmission respectively; 4% cases vs. 13% controls knew about preventive vaccination. Logistic regression revealed that H/o jaundice, family H/o hepatitis B, blood transfusion, hospitalization and migration were independent risk factors for HBV transmission (OR=4.69, 6.55, 3.89. 2.49 and 2.76 respectively) Conclusions: Screening and awareness programs for rural adults necessary to identify and follow up those with H/o jaundice, HBV+ contacts and migrant population. Infection control and biomedical waste management need strengthening.